Q. 2 C4.7( 3 Votes )

# Let A = {1, 2, 4,

B–C is defined as {x ϵ B : x C}

B = {2, 3, 5, 6}

C = {4, 5, 6, 7}

B–C = {2, 3}

(A (B – C)) = {x:x ϵ A and x ϵ (B – C)}

= {2}

R.H.S:

(A B) = {x:x ϵ A and x ϵ B}

= {2, 5}

(A C) = {x:x ϵ A and x ϵ C}

= {4, 5}

(A B) – (A C) is defined as {x ϵ (A B) : x (A C)}

= {2}.

Hence Verified.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Let A = {a, b, c,RS Aggarwal - Mathematics

If A and B be twoRS Aggarwal - Mathematics

(i) If A <span laRS Aggarwal - Mathematics

Using propeMathematics - Exemplar

If A and B are twRS Aggarwal - Mathematics

In a town of 10,0RS Aggarwal - Mathematics

If A and B are twRS Aggarwal - Mathematics

If <a name="MTBlaRS Aggarwal - Mathematics

If n(A) = 3 and nRS Aggarwal - Mathematics

For any sets A, BRS Aggarwal - Mathematics